Chronic Recurrent Multifocal Q Fever Osteomyelitis in Children: An Emerging Clinical Challenge. Issue 9 (September 2016) - Francis, Joshua R.; Robson, Jennifer; Wong, David; Walsh, Mark; Astori, Ivan; Gill, David; Nourse, Clare
Abstract : Background: Clinical disease caused by Coxiella burnetii occurs infrequently in children. Chronic Q fever is particularly uncommon and endocarditis is rarely seen. A small number of cases of Q fever osteomyelitis have been described but the pathophysiology is not well understood and optimal treatment is unknown. Methods: We describe a series of cases of chronic recurrent multifocal Q fever osteomyelitis cases diagnosed in children from a single region in Australia. Results: Between 2011 and 2014, 9 cases of chronic recurrent multifocal Q fever osteomyelitis were diagnosed based on clinical findings, suggestive serology and detection of C. burnetii DNA by polymerase chain reaction testing of biopsy samples (8/9). All required surgical management; antibiotic and adjuvant therapies did not appear to be consistently effective and 2 cases had clinical resolution in the absence of directed antimicrobial therapy. Conclusions: Chronic recurrent multifocal osteomyelitis is a rare manifestation of chronic Q fever infection in children. The pathophysiology of this condition is poorly understood, and effective treatment options have not been established. Abstract : Supplemental Digital Content is available in the text.